KONDISI SOSIAL EKONOMI KELUARGA PENAMBANG EMAS ILEGAL DI DESA PINTU GOBANG KARI KECAMATAN KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI - Gusmelia Sari; T. Romi Marnelly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This research was conducted in Pintu Gobang Kari Village, Central Kuantan District, Kuantan Singingi Regency, Riau Province. The purpose of this study was to determine: 1) The socioeconomic conditions of the family before and after becoming an illegal gold miner in Pintu Gobang Kari Village, Kuantan Tengah District, Kuantan Singingi Regency. 2) Knowing the social relationship of the family of illegal gold miners with the community and other fellow gold miner families in Pintu Gobang Kari Village, Central Kuantan District, Kuantan Singingi Regency. To achieve this goal, a descriptive qualitative research method was used by taking 4 people as the main informant and 1 person as the key informant (Key Informant). This study uses purposive sampling technique through observation, interviews, and documentation. The results of research on socio-economic conditions seen from the education of the head of the mining family are still relatively low, this is one of the reasons they do illegal work. Judging from the income before and after becoming miners, the family of gold mining workers has experienced many improvements, one of which is that their children are able to take education up to university level thanks to their income as gold mining workers. In terms of health, the families of illegal gold mining workers have sought treatment for treatment at hospitals, doctors and others if their family members get sick. The results of the research on the social relations of illegal gold miner families with the community as well as other gold miner families have been going well, reflected in the form of interaction and involvement in social gathering, organization, spiritual activities, and the nature of helping in the events of the journey of human life. Keywords: Socio-Economic, Illegal Gold Mining, Social Relations